'Strike Breaking, Union Breaking, Intolerance and Bigotry': Irish Working-Class Perceptions of Fascist Italy in the 1920s. Issue 1 (April 2019) - Phelan, Mark
Abstract : This article examines the impact of the first fascist power, Italy, on Irish working-class opinion in the early years of the independent Irish state. While labour had played an important role in the Irish Revolution (1913–21), it also benefited from the wartime boom in Irish agriculture and industry. The trade unions therefore entered the independence era in a strong position, which signalled inevitable conflict with the reactionary Cumann na nGaedheal regime that superseded the British withdrawal. Meanwhile, Irish industrial politics evolved against the backdrop of extensive interest in Italian fascism. Because Mussolini was widely admired as a 'Catholic' statesman, he was revered by powerful sections of Irish society, in particular a domineering clergy that fulminated against communism and liberalism. For this reason Italian developments featured heavily in Irish discourses that were far less insular than historians commonly presume. Accordingly, uneasy labour activists felt genuinely haunted by the spectre of fascism, even if, in reality, the threat to Irish democracy was overstated.